Genetic effects on chromatin accessibility uncover mechanisms of liver gene regulation and quantitative traits - Currin, Kevin W.; Perrin, Hannah J.; Pandey, Gautam K.; Alkhawaja, Abdalla A.; Vadlamudi, Swarooparani; Musser, Annie E.; Etheridge, Amy S.; Broadaway, K. Alaine; Rosen, Jonathan D.; Varshney, Arushi; Chaudhry, Amarjit S.; Gallins, Paul J.; et al. (Genome Research, 2025)
Chromatin accessibility quantitative trait locus (caQTL) studies have identified regulatory elements that underlie genetic effects on gene expression and metabolic traits. However, caQTL discovery has been limited by small sample sizes. Here, we map caQTLs in liver tissue from 138 human donors and identify caQTLs for 35,361 regulatory elements, including population-specific caQTLs driven by differences in allele frequency across populations. We identify 2126 genetic signals associated with multiple, presumably coordinately regulated elements. Coordinately regulated elements link distal elements to target genes and are more likely to be associated with gene expression compared with single-element caQTLs. We predict driver and response elements at coordinated loci and find that driver elements are enriched for transcription factor binding sites of key liver regulators. We identify colocalized caQTLs at 667 genome-wide association (GWAS) signals for metabolic and liver traits, and annotate these loci with predicted target genes and disrupted transcription factor binding sites. CaQTLs identify threefold more GWAS colocalizations than liver expression QTLs (eQTLs) in a larger sample size, suggesting that caQTLs can detect mechanisms missed by eQTLs. At a GWAS signal colocalized with a caQTL and an eQTL for TENM2, we validated regulatory activity for a variant within a predicted driver element that is coordinately regulated with 39 other elements. At another locus, we validate a predicted enhancer of RALGPS2 using CRISPR interference and demonstrate allelic effects on transcription for a haplotype within this enhancer. These results demonstrate the power of caQTLs to characterize regulatory mechanisms at GWAS loci.